2021
DOI: 10.4103/jips.jips_79_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical success between tilted and axial implants in edentulous maxilla: A systematic review and meta-analysis

Abstract: Aim: This systematic review and meta-analysis evaluated the clinical survival of axial and tilted implants in atrophic edentulous maxilla after three years of immediate loading and also the corresponding marginal bone loss. Setting and Design: This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines (PRISMA). Materials and Methods: The relevant studies were retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Group 3 implants, which were installed with a vertical angle of more than 20°, had about one-quarter of the marginal bone resorption of Group 1 at their first-year radiographic evaluation. Several previous studies have shown that tilting an implant does not affect its survival or marginal bone resorption 7 - 13 . However, we found that intentional tilting not only did not affect implant survival, but also reduced the mean peri-implant bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Group 3 implants, which were installed with a vertical angle of more than 20°, had about one-quarter of the marginal bone resorption of Group 1 at their first-year radiographic evaluation. Several previous studies have shown that tilting an implant does not affect its survival or marginal bone resorption 7 - 13 . However, we found that intentional tilting not only did not affect implant survival, but also reduced the mean peri-implant bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…The primitive concept advocated the use of implant placement that was "in-line" or perpendicular to occlusal stresses and claimed that tilted implants would lose bone and eventually "de-osseointegrate". (Mehta et al, 2021) However, another technique for treating atrophic edentulous maxilla using titled implants was discovered to be a possible therapeutic option because of technological advancements. (Morton et al, 2018) Its goal was to get maximum cortical bone involved for support.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Unlike these procedures, which involved a deferred load, in Group C, in accordance with several prior research results, patients were subjected to immediate loading [25,26].…”
Section: Prosthetic Protocolmentioning
confidence: 99%